Koncepcja zmiany strategii przedsiębiorstwa - Wołczek, Przemysław (The concept of a change of an enterprise strategy, 2006)
The paper presents the concept of a change of an enterprise strategy. Nowadays enterprises operate in a very turbulent, dynamic and changeable environment. These features of the environment result in the necessity to constantly observe changes which take place in the enterprise environment, and skilfully predict the direction of those changes in the future and adjust to them in order to stay on the market. We may say that enterprises must be ready to change their strategies in order to keep up with fast changes in environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 177-188